Empirical modeling and experimental validation of gas-to-liquid heat pipe heat exchanger with baffles - Kang, Sukkyung; Kim, Kyuil; Seo, Jin Hyeuk; Lee, Jungho (Energy, 2024)
Empirical modeling of heat pipe heat exchangers (HPHX) is the most economical and appropriate method for predicting its performance and estimating long-term economic benefits in the industrial field. Unfortunately, no models can predict the performance of HPHX with baffles that show complex flow characteristics, such as a combined flow arrangement of parallel flow and counterflow. This study presents the empirical model for HPHX with baffles, which predicts thermal performance and pressure drop based on empirical correlations and theoretical relations. It fabricated the HPHX with baffles composed of 95 copper two-phase closed thermosyphons (TPCTs) and measured its effectiveness, heat transfer rate, and pressure drop. We validated the presented model based on our experimental results and literature data. The validation results confirm that it can predict the HPHX performance with high accuracy, not only for the presence of baffles but also for various HPHX geometries (heat exchanger dimensions, number of baffles, etc.) and operating conditions (temperature and flow rate of hot and cold fluids). Finally, we analyzed and discussed the composition of HPHX performance, and as a result, enhancing forced convection between the working fluid and the TPCT bundle is a vital key to improving thermal performance, especially for HPHX that utilize gas (or air) as the working fluid. It was also found that the wall material had a negligible impact on thermal performance, so it was reasonable to consider stainless steel, which is more resistant to corrosion and erosion than copper. Our results are expected to be a great reference for engineers designing and manufacturing HPHX in the industrial field.
Keywords: Baffle; Empirical model; Experimental validations; Heat exchanger performance; Heat pipe heat exchangers; Industrial fields; Performance; Thermal Performance; Two-phase closed thermosyphon; Working fluid; Baffle; Empirical modeling; Experimental validation; Heat pipe heat exchanger